Effects of Cassava Chips Fermentation Conditions on The Produced Flour Properties - Angina Meitha; Yazid Bindar; M.T.A.P. Kresnowati (ASEAN Journal of Chemical Engineering, 2016)
A fermentation process to produce soft-texture and low cyanogenic content cassava flour had been studied, in particular the effects of temperature, circulation of the fermentation media, and chips size, on fermented cassava flour (fercaf) properties. Fermentation was shown to affect properties of cassava flour: reducing the cyanogenic content, swelling power, as well as solubility, whereas on the other hand increasing the amylose content and correspondingly the measured DE. Further, the properties of the produced flour were affected by the implemented fermentation operation conditions. Fermentation temperature was found to significantly affect amylose content. Media circulation was found to significantly affect the measured Dextrose Equivalent. On the other hand, the size of cassava chips significantly affected the cyanogenic content and solubility of the flour